Prevalence of dental caries in Pakistan: a systematic review and meta-analysis - Ammar Ahmed Siddiqui; Freah Alshammary; Mushir Mulla; Saad M. Al-Zubaidi; Eman Afroze; Junaid Amin; Salman Amin; Sameer Shaikh; Ahmed A. Madfa; Mohammad Khursheed Alam (BMC, 2021)
Abstract Background Optimum oral health is impossible to achieve without managing dental caries. The first step to manage dental caries at a community level is to know its prevalence and trend. Unfortunately, the prevalence of dental caries at the national/regional level is not known in many developing countries. Pakistan is no exception. The present meta-analysis was planned to document the prevalence of dental caries at the national, as well as regional level. This paper will serve as a baseline for making future health policies, and health promotion activities in the country. Methods Literature was searched through various databases, such as PubMed, SCOPUS, and Web of science using: "Prevalence", "Dental Caries", "Dental Decay" and "Severity" as keywords. Any study that reported the prevalence of dental caries, and was conducted in the Pakistani population was included. Thirty studies fulfilled the inclusion criteria. Quality assessment of all the included studies was performed using Joanna Briggs Institute (JBI) critical appraisal checklist for prevalence studies. MedCalc software was used to analyze the data. Results In total 27,878 subjects were included in a meta-analysis from 30 studies. The prevalence estimate of dental caries at the national level was 56.62% (95% CI: 49.54 to 63.57). The I2 value was 99.07% (95% CI: 98.94 to 99.18), (I2 > 75%) indicating heterogeneity, hence pooled proportion was reported using a random-effect model. The prevalence estimate of dental caries in Sindh was 58.946% (95% CI: 43.796 to 73.274), and in Punjab, it was 55.445% (95% CI: 44.174 to 66.44), whilst in Baluchistan and KPK combined was 51.168% (95% CI: 22.930 to 79.004). Conclusion Based on the existing data nearly 60% of the Pakistani population have dental caries. The proportion is almost the same in all provinces. Most of the included studies were found to be of high risk.